2021
DOI: 10.1080/15555240.2021.1922286
|View full text |Cite
|
Sign up to set email alerts
|

The role of lifestyle on NHS ambulance workers’ wellbeing

Abstract: The role of lifestyle on mental health in the ambulance worker population is unclear. The aim of this paper is to explore the role and impact of lifestyle on the mental health of ambulance workers within the United Kingdom (UK). Participants (N ¼ 160) were recruited from 4 NHS ambulance trusts in England. Data were collected on lifestyle factors (sleep, physical activity and alcohol use) and mental health outcomes (trauma, anxiety, depression and stress); these were assessed by use of various questionnaires in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(51 reference statements)
0
2
0
Order By: Relevance
“… 17 , 18 A study among paramedics found that sleep and physical activity explained a significant level of variance in trauma response (35%), indicating likely protective effects of such behaviours and the role of lifestyle interventions as a potentially feasible first-line mental health strategy. 19 , 20 Another study found that exercise participation and high cardiorespiratory fitness can help police officers to better cope with chronic stress and subsequently take less sick leave. 21 …”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 A study among paramedics found that sleep and physical activity explained a significant level of variance in trauma response (35%), indicating likely protective effects of such behaviours and the role of lifestyle interventions as a potentially feasible first-line mental health strategy. 19 , 20 Another study found that exercise participation and high cardiorespiratory fitness can help police officers to better cope with chronic stress and subsequently take less sick leave. 21 …”
Section: Introductionmentioning
confidence: 99%
“…Physical activity and its structured subset, exercise, can improve mood and reduce psychiatric symptoms among people with diagnosed mental disorders as well as subclinical populations experiencing mental health symptoms (16, 17). A study among paramedics found that sleep and physical activity explained a significant level of variance in trauma response (35%), indicating likely protective effects of such behaviours and the role of lifestyle interventions as a potentially feasible first-line mental health strategy (18, 19). Emergency service workers require tailored interventions to help overcome some of the adverse health consequences of their work and targeting lifestyle behaviours may be a less stigmatising and culturally acceptable strategy compared to traditional mental healthcare (20).…”
Section: Introductionmentioning
confidence: 99%